Acute Horner syndrome from supraclavicular lymphadenopathy as the first manifestation of metastatic lung carcinoma - Hohs, Kathryn; Morettin, Christina (Canadian Journal of Optometry, 2025)
Introduction Horner syndrome is a rare ocular condition consisting of pupil miosis, eyelid ptosis and facial anhidrosis. It occurs secondary to damage along the three-neuron sympathetic nerve pathway that travels a long course from the brain to the eye. If acute, the syndrome can be the presenting sign of life-threatening pathology in the head, chest, or neck. Thorough history, careful clinical exam, and proper imaging studies are essential to diagnose the syndrome, help localize the lesion and determine proper treatment for the underlying etiology. Case Report This case presents a 62-year-old female patient with an acute left-sided Horner syndrome confirmed by pharmacologic testing. She had an unremarkable medical history beyond arthritis, denied a history of trauma, and reported a tobacco smoking history. Further review of symptoms did not allow for definitive localization of the lesion, nor did she have a known underlying cause of Horner syndrome at presentation. Emergent imaging of the chest and neck revealed a preganglionic lesion caused by metastatic supraclavicular lymphadenopathy in the neck originating from primary lung carcinoma. Brain magnetic resonance imaging identified several areas of metastasis to the brain. She was treated with prompt chemotherapy and radiation. Conclusion An adult patient with acute Horner syndrome without significant localizing symptoms or pertinent review of systems requires an emergent and thorough work up to rule out malignancy. Horner syndrome as the first presenting sign of undetected malignancy along the sympathetic chain is rare. An accurate diagnosis from an optometrist and subsequent timely referral is critical to uncover potentially life-threatening pathology that may be unknown to the patient at the time of presentation.